QUANTITATIVE METHODS OF FINANCIAL STABILITY DEPENDENCE ON THE COMPANY VALUE - M. A. Fedotova; T. V. Tazihina; A. S. Maltsev (Стратегические решения и риск-менеджмент)
The topics related to the financial stability assessment and market valuation of a business have received a detailed coverage in contemporary literature. However no approaches in meth-odology have been elaborated that would enable the quantitative assessment of the degree to which the financial stability indices and the market value of the company are linked together. Therefore, the econometric modelling of the dependence assessment between the cost factors and financial stability indicators poses a task relevant to present-day challenges.The authors of the article present the proof that the company value is an integral indicator, which can replace the broad range of absolute and relative financial stability ratios in the assessment of the financial stability of a business.Based on the econometric data analysis of the leading Russian and global energy companies that meet the profitability, financial stability and maturity criteria, the article proves the practical application of Modigliani—Miller theory as compared to D. Duran traditional theory of capital structure. The econometric regression correlations and the analysis of their statistical significance bring the con clusion of the ambiguity in the correlation between the Cost of Capital and Financial Leverage.